Analisis Portal Repository Tugas Akhir Mahasiswa (RAMA) Repositori Ristekdikti - Hadira Latiar; Nining Sudiar; Rosman (Universitas Lancang Kuning, 2023)
Rama Ristekdikti is an integrated portal with institutional repositories in Indonesia that functions as information technology-based scientific communication. The number of institutional repositories on the Rama Ristekdikti portal is 171, this number is not comparable to the number of universities in Indonesia, which are 4,670 universities. From this, it is necessary to conduct further research on the Rama Ristekdikti portal. The method in this research is descriptive quantitative, data collection techniques by observation and literature study. While the data analysis using the percentage equation. The results of this study are obtained 170 repositories registered in the Rama Ristekdikti portal, 9 institutions have not yet known the webometric ranking. The development of the largest institutional repository in East Java province, both private and public. The applications used are dominated by 154 E-prints, while the majority of the languages ​​used are English. The most common type of content is student's final project. Meanwhile, the most documents uploaded to institutional repositories are Universitas Gadjah Mada. From the results of the discussion, there are several recommendations that can be given regarding the development of the Repository portal. Institutions should apply institutional repositories for those who have not applied, and institutions that have applied institutional repositories should immediately be integrated with the Rama Ristekdikti portal.